Testing and numerical modelling of S690 high strength steel welded I-sections under compression - Tan, Hui Qi (2019)
An extensive study on S690 high strength steel welded I-section is carried out in this particular study, including an experimental testing and numerical modelling on the material properties and cross-section compression capacities of welded I-sections manufactured from steel plates of grade S690. Eight different welded I-sections fabricated through gas metal arc (GMA) welding were utilised in the testing. The testing programme included material coupon tests, initial geometric imperfection measurements, residual stress measurements and a total of sixteen stub column tests. Through this testing, a newly proposed predictive model is developed for the residual stress distribution pattern in S690 welded I-sections. Subsequently, a numerical study involving finite element simulation was carried out, to validate the developed numerical models against the experimental testing results, and subsequently used to conduct further parametric studies to expand the data pool covering a wider range of dimensions. Thereafter, the experimental and numerically obtained load-carrying capacities were then employed to evaluate the accuracy of three existing design codes, in their respective provisions of slenderness limits and local buckling design. The three design codes evaluated were the European, American and Australian standards, catered to S690 welded I-sections in compression. Through this evaluation, it be deduced that the slenderness limits provided by the codes are overall quite accurate in the cross-section classification of S690 welded I-sections. The codified provisions for local buckling design were also found being able to obtain generally accurate predictions of compression resistances, with the closest accuracy obtained from the American standards.